If f(x) = 4x - 3, show that f(2x) = 2f(x) + 3

Dolly Robinson 2020-11-01 Answered
If f(x) = 4x - 3, show that f(2x) = 2f(x) + 3
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

liannemdh
Answered 2020-11-02 Author has 106 answers
Given that the function f(x)=4x−3
Plugging x=2x both sides we have
f(2x)=4(2x)−3
=8x−3
=2(4x−3)+3
=2f(x)+3
Therefore, we get
f(2x)=2f(x)+3
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions